EFFICACY OF CERTAIN BOTANICAL INSECTICIDES AGAINST SHOOT AND FRUIT BORER, LEUCINODES ORBONALIS (GUENEE) ON BRINJAL (SOLANUM MELONGENA L.) - RAMAWTAR YADAV,; HEMANT LYALL, SANJAY KUMAR,; RAMESH KUMAR SANP, (The Bioscan, 2015)
Field experiments were carried out during Rabi season of 2013-14 on relative efficacy of different botanical products with an insecticide for shoot and fruit borer (Leucinodes orbonalis) of brinjal. The result showed that the four applications of Cypermethrin 0.05%, Pungam oil 2%, Nimbicidene 0.4% and Iluppai oil 2% was found at par each other most effective. Which caused lowest mean infestation of shoot damage, (5.80, 5.88, 6.86 and 7.13) per cent, and Cypermethrin 0.05% and Iluppai oil 2% fruit infestation was recorded (10.29 and 10.63) per cent. It was followed by Neem oil 2% and NSKE 5%, (9.07 and 10.26) per cent mean infestation of shoot, respectively and were at par with each other and the Nimbicidine 0.4% and Pungam oil 2% observed (11.97 and 11.98) per cent fruit damage at par each other, and followed by Neem oil 2%, NSKE 5% and garlic extract 3% were found moderately effective being (15.12, 16.45 and 18.82) per cent fruit damage, respectively.